Pictured are: Peggy Casey, New York State College... - University at Albany (University Photograph Collection)
Pictured are: Peggy Casey, New York State College for Teachers, Class of 1945, Bob Sullivan, New York State College for Teachers, Class of 1946, and Hal Weber, New York State College for Teachers, Class of 1947.